Difficulties in the differential diagnosis of pneumonia complicated by an abscess and a limited variant of Wegener's granulomatosis - M. D. Romanov (Tuberkulez i Bolezni Lëgkih, 2019)
The article presents a clinical case that confirms the importance of careful collection and analysis of medical history and active identification of pathology of the upper respiratory tract, middle ear and eyes typical of the debut of Wegener's granulomatosis. It demonstrates the need for early testing of level of antibodies to the neutrophil cytoplasm in the blood serum (ANCA) and biopsy in the target organs giving the preference to less invasive transnasal biopsy. The positive results of early comprehensive immunosuppressive ex juvantibus therapy confirm the diagnosis of Wegener's granulomatosis.